A strategy paper for a concept on a non-legally binding instrument on all types of forests - Thomas W. Schneider (Federal Research Centre for Forestry and Forest Products (BFH), Institute for World Forestry, 2006)
At UNFF-6 the Chairman's Text/Resolution emphasized the importance of strengthening political commitment and action at all levels to implement effectively the sustainable management of all types of forests and to achieve the global objectives set out in the resolution, by requesting the United Nations Forum on Forests to conclude and adopt at its seventh session a non-legally binding instrument (NLBI) on all types of forests. The following paper has to be seen as a Strategy Paper for a Concept on a Non-legally binding instrument for Sustainable Forest Management/ of /on all types of forests.
urn:nbn:de:gbv:253-200912-dk038951-1
Keywords: 630